Altruistic Value Reflection Company Policy and Strategy: Finding Local Wisdom and the Meaning of CSR - Darwis Said; Asriani Junaid (Pusat Penerbitan dan Publikasi Ilmiah, FEB, Universitas Muslim Indonesia, 2020)
This research focuses on exploring the values in company activities that can be justified as a form or model for implementing corporate social responsibility (CSR). Data collection was carried out through interviews, field observations, and literature studies. While data analysis was carried out using an ethnomethodological approach. This study indicates that incorporating business practices, through the organizational structure model and several CSR strategies and policies reflect the existence of altruistic values , which are a form or model of CSR implementation. This can be seen in an organizational structure with the Town Service Department, External Relations Department, and Environmental, Health, and Safety Department (EHS). Activities and corporate culture that have a holistic dimension are guided by a vision, concern, jointness (in responding to and overcoming problems), and always learning and taking advantage of every accident. The results of this study indicate a meeting point between business interests and socio-environmental interests. There is a process of transforming knowledge of the company's sand culture on the behavior and way of thinking of the company's people.